Transient binocular blindness: A rare presentation of aortic dissection - Azizul Fadzli, Wan Jusoh@Ab Rahim; Nik Ahmad Shaiffudin, Nik Him; Rosliza, Yahaya; Nik Arif, Nik Mohamad (2018)
Introduction: Aortic dissection is a clinical chameleon that can have variable presenting features that require a careful history and physical examination. A non-specific presentation of this life-threatening condition causes a diagnostic dilemma among clinicians especially in the emergency department leading to grave consequences. Case Presentation: We present a case of aortic dissection that presented as an acute bilateral blindness that was associated with a sudden onset of loss of consciousness and central chest pain. Bedside carotid ultrasound showed a double lumen carotid artery suggesting an intraluminal flap. Computed tomography angiography revealed extensive dissection of the entire length of the aorta. Discussion: This case illustrated the need for a high index of suspicion to diagnose patients with aortic dissection especially as the patient presented with an acute binocular visual loss and chest pain. Conclusion: A bedside carotid artery ultrasound in the emergency department was found useful in screening and diagnosing a carotid artery–related pathology.